2011
DOI: 10.5268/iw-1.1.406
|View full text |Cite
|
Sign up to set email alerts
|

Ecological impacts of excessive water level fluctuations in stratified freshwater lakes

Abstract: The paper refers to the contemporary sensitivity of a ribbon flow-through lake to changeable meteorological conditions (precipitation, evaporation). We checked whether the lake morphology can affect the abrupt changes in hydrological conditions under which environmental changes occur. We analyzed changes in the level and extent of the water table in relation to morphological thresholds of a Charzykowskie Lake. Changes in the lake water level were disproportionate in relation to small changes in the volume of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
282
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 345 publications
(294 citation statements)
references
References 66 publications
8
282
1
3
Order By: Relevance
“…Many studies have been conducted to assess the influence of WL variations on the community of fish or other aquatic organisms (Pompeu, Godinho, 2006;Paulovits et al, 2007;Baumgärtner et al, 2008;Zohary, Ostrovsky, 2011;Dutterer et al, 2013). These studies demonstrated that both the fluctuations of water levels in natural environments (caused by annual cycle and climate change), as well as in reservoirs and other artificial water bodies, promoted impacts on the fish communities and other components of the aquatic biota, as well as in water quality parameters.…”
Section: E160084[2]mentioning
confidence: 99%
“…Many studies have been conducted to assess the influence of WL variations on the community of fish or other aquatic organisms (Pompeu, Godinho, 2006;Paulovits et al, 2007;Baumgärtner et al, 2008;Zohary, Ostrovsky, 2011;Dutterer et al, 2013). These studies demonstrated that both the fluctuations of water levels in natural environments (caused by annual cycle and climate change), as well as in reservoirs and other artificial water bodies, promoted impacts on the fish communities and other components of the aquatic biota, as well as in water quality parameters.…”
Section: E160084[2]mentioning
confidence: 99%
“…<4.5 m, compared to Valdovinos et al, 2007;Zohary and Ostrovsky, 2011;Eloranta et al, 2016), is expected to reduce occupation of the littoral zone by native species in the presence of the introduced rainbow trout (Hanisch et al, 2012;Otturi et al, 2016). However, the abundant large rocks and semisubmerged coastal trees present in the Alicurá reservoir seem to provide the necessary structure and refugia for native species, as revealed by the observation of P. trucha less than 10 cm in length using the shallow littoral in protected bays, along with G. maculatus and juvenile ERT (D. Nabaes Jodar, unpublished data).…”
Section: Discussionmentioning
confidence: 92%
“…We did not consider the "water level stability" as single factor, but we considered it between the threats, according to Keto et al (2006) and Zohary and Ostrovsky (2011) indicating that drastic water level fluctuations (fluctuations out from the normal cyclical ranges) are disadvantageous for aquatic species. Also, waters coming not from the natural water cycle ("alien waters inputs") was considered as threat for similar reasons and for their relative pollution risks.…”
Section: Ecological Assessment Proceduresmentioning
confidence: 99%